Spinal cord sparing reirradiation with helical tomotherapy - Sterzing, Florian; Hauswald, Henrik; Uhl, Matthias; Herm, Hendrik Alexander; Wiener, Andreas; Herfarth, Klaus; Debus, Jürgen; Krempien, Robert (Cancer, 2010)
BACKGROUND: The purpose of this study was to present planning, feasibility, toxicity, and outcome of helical tomotherapy for spinal cord-sparing reirradiation of spinal metastases and tumors. METHODS: Thirty-six patients with spinal metastases and tumors who had undergone previous radiotherapy were reirradiated with helical tomotherapy because of tumor progression, pain, or compromised stability. Mean spinal cord dose of previous radiotherapy was 36.3 grays (Gy) after a median time interval of 17.5 months. Mean prescribed dose of reirradiation was 34.8 Gy. Daily megavoltage computed tomography (CT) image guidance was performed to assure precise dose application. RESULTS: Mean beam time was 8.4 minutes; the dose maximum to the spinal cord at reirradiation could be limited to a 9.8-Gy median dose (minimum, 5.2 Gy; maximum, 21.8 Gy). Significant pain relief from a median value of 7 on the visual analogue scale before therapy to a median value of 3 at 6 weeks after radiotherapy was achieved. One- and 2-year local control was 76% and 63%; overall survival was 67% after 1 year and 58% after 2 years. One grade 2 skin toxicity and no grade 3 or higher toxicities were observed. CONCLUSIONS: Helical tomotherapy makes reirradiation of spinal metastases and excellent avoidance of the spinal cord possible and achieves good pain relief and local control. With a minimal distance of several millimeters between target volume and spinal cord, tailor-made dose distributions with steep dose gradients around previously irradiated tissue are obtained and precisely applied with daily megavoltage CT-based image guidance. Cancer 2010. © 2010 American Cancer Society.